Numerical Investigation on the Thermal Protection Characteristics of a New Active Jet Design Parameter for Hypersonic Flight Vehicle - Songyan Tian; Yanhui Duan; Hongbo Chen (International Journal of Aerospace Engineering)
This study investigated the thermal protection performance of an active jet thermal protection system (PRsAJ-TPS) based on a new jet design parameter PRs for hypersonic flight vehicles (HFVs). The new parameter PRs is defined as the relationship between the jet flow total pressure and the free flow total pressure behind the outer bow shock. A 20° tilted nozzle design is employed together with the PRs to form the PRsAJ-TPS. Theoretical and numerical analysis is performed to prove the advantages of using the PRs. A conventional in-house CFD solver with the k‐ω SST turbulence model is utilized to perform the calculation. The influence of different PRs (working in the short penetration mode) and flight angles of attack on the performance of the PRsAJ-TPS is also studied. The simulation results confirmed that with a constant PRs, the Mach disk location stays the same and the normalized heat flux reduction is similar at different flight conditions. Nearly linear relationships exist between the new design parameter PRs and thermal protection performance indicators. The PRsAJ-TPS also exhibits good protection when flight angle of attack (AoA) varies between 0° and 40°, with the best results achieved at AoA=0°. This study provides valuable information for the engineering application of the jet-based TPS to future HFVs.